Identity privacy and security protection scheme for charitable donations based on group signatures - LIU Biao; WANG Zhizhong; YUAN Xiqin; FENG Huamin (Tongxin xuebao)
To address digital privacy leakage and balance anonymity with accountability in charitable donations, the identity privacy and security protection scheme for charitable donations based on group signatures was proposed. Specifically, a traceable group signature framework was proposed, a lightweight authentication protocol tailored to donor requirements in charitable scenarios was designed, and a dynamic Hash graph storage architecture was introduced to optimize supply chain management alongside a digital certificate distribution mechanism. Security analysis conducted under the random oracle model demonstrated that existential unforgeability against chosen message attacks (EUF-CMA) was achieved, resolving multiple security vulnerabilities in existing systems including user anonymity flaws and information privacy leakage. Theoretical analysis and experimental evaluation revealed that the proposed scheme improved efficiency by up to 12 times for user requests and 1.5 times for donor institutions. This approach significantly reduces computational and time overhead compared to current charitable donation mechanisms.